Nikos Kazantzakis, un pensador de nuestro tiempo - Stassinakis, Georges (Byzantion Nea Hellás, 2015)
Professor Stassinakis, Presiden! of the Société Internationale des Amis de Nikos Kazantzakis presents a summary of diverse aspects of the Greek writer’s personality and work. Stassinakis’ study has three sections: a) Introduction and analisys of Kazantzakis’ thought b) His active presence in society e) The man of the approach between the peoples and the synthesis. -Befare the exposition of the three themes, the author numbers the writer’ s work, which is only partially known in our language. In the summarizing of Kazantzakis thought, the author highlights his search for freedom, his veneration for Nature and the primacy of the spirit in his work. Besides highlighting the Cretan root of his personality and creation, the author studies the effort for the approach between the peoples, by means of his voyages, his translations, his writings and his different activities. The article brings a global vision about the Creten writer and his work.